2021
DOI: 10.4012/dmj.2020-231
|View full text |Cite
|
Sign up to set email alerts
|

Finite element simulation of fixed dental prostheses made from PMMA —Part II: Material modeling and nonlinear finite element analysis

Abstract: Material characteristics can change significantly with increasing chewing velocity. As these in-vitro examinations are very timeconsuming and cost-intensive, the application of finite element analysis (FEA) offers a suitable alternative for predicting the material behavior of complex specimen geometries under clinically relevant loads. Although FEA is applied within numerous dental investigations, there are only few studies available in which a nonlinear FEA is validated with real experiments. Therefore, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…This study shows that PMMA exhibits predominantly linear behavior compared to the other analyzed structures, exhibiting stress relaxation, plastic deformation and a modulus of elasticity dependent on the load and rate of load application. The plastic deformation of PMMA under different degrees of pressure could improve the obtained results; although, this would considerably increase the experimental stress, which is why it is necessary to implement compression tests [43]. The 3D FEA simulation used in this study confirmed that a heavier and stiffer material is not more resistant to forces or deformations, since it transfers more stresses to supporting structures, while the opposite occurs with more flexible and resilient materials [44].…”
Section: Discussionmentioning
confidence: 66%
“…This study shows that PMMA exhibits predominantly linear behavior compared to the other analyzed structures, exhibiting stress relaxation, plastic deformation and a modulus of elasticity dependent on the load and rate of load application. The plastic deformation of PMMA under different degrees of pressure could improve the obtained results; although, this would considerably increase the experimental stress, which is why it is necessary to implement compression tests [43]. The 3D FEA simulation used in this study confirmed that a heavier and stiffer material is not more resistant to forces or deformations, since it transfers more stresses to supporting structures, while the opposite occurs with more flexible and resilient materials [44].…”
Section: Discussionmentioning
confidence: 66%
“…This target can then be used to select a failure criterion of fracture strains at different strain rates from the proposed P(ε,ε̇) model, similar to the previously described application. By simulating the desired component (akin to Schrader et al 17) ) at the expected boundary conditions (i.e., chewing velocity and chewing force in the case of a dental restoration), one obtains an indication of whether the planned supply can withstand the expected load . If the simulated component happens to fracture, the restoration must be redesigned; otherwise, the planned restoration can be manufactured.…”
Section: Discussionmentioning
confidence: 99%
“…The tests are conducted on polymer-based biomaterials to ultimately increase patient safety and comfort by predicting the failure probability of restorations in consideration of rate-dependent material behavior. An implementation of finite element models, such as the simulation of dental prostheses by Schrader et al 17) is deemed worthwhile. It should be noted in advance that although we focused on dental PMMA in this study, the methodology developed in this study is considered usable for all kinds of above-mentioned dental biomaterials and other thermoplastics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation